PROBLEM BASED LEARNING: NEW STRATEGY TO TEACH DESCRIPTIVE TEXT IN SPEAKING - Sari, Dwi Rosita (Lingual Journal of Language and Culture, 2020)
The aims of research are (1) The implementation of Problem Based Learning strategy to teach speaking  descriptive text (2) To find the problems of Problem Based Learning strategy to teach speaking descriptive text (3) To know the solutions of the Problem Based Learning strategy to teach speaking descriptive text. The type of this research is descriptive qualitative research and researcher uses case study in answering the problem of the research. This research takes the seventh grade students of SMPN 1 Bendo, Kabupaten Magetan in term 2018/2019. The result s of research show that the implementation Problem Based Learning strategy to teach speaking descriptive text are (1) by explaining the materials while the students do the task in pair and (2) by giving steps in teaching learning process ( pre-activities,whislt-activities and post-activities ) . The problem of Implementation of PBL strategy are (1) some students are difficult to translate from Indonesian in to English and (2) some students need more time to do the task. Meanwhile, solution  of the implementation of PBL strategy to teach speaking are (1) The teacher give s more time to the students doing the task ; (2) S tudents cooperate each other with friends ; (3) The students use the real thing.